2014
DOI: 10.1371/journal.pone.0089240
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation in the TECTA Gene in a Chinese Family with Autosomal Dominant Nonsyndromic Hearing Loss

Abstract: TECTA-related deafness can be inherited as autosomal-dominant nonsyndromic deafness (designated DFNA) or as the autosomal-recessive version. The α-tectorin protein, which is encoded by the TECTA gene, is one of the major components of the tectorial membrane in the inner ear. Using targeted DNA capture and massively parallel sequencing (MPS), we screened 42 genes known to be responsible for human deafness in a Chinese family (Family 3187) in which common deafness mutations had been ruled out as the cause, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
4
1
Order By: Relevance
“…This HL deterioration rate is comparable to the hearing deterioration rate in a normal hearing control population. A previous report stated that patients with TECTA -associated mid-frequency HL might be prone to presbycusis as they are theoretically exposed to a lower level of sound energy as a result of cochlear amplification deficiency [36,37]. However, our results indicated that the hearing loss progression rate was the same as in the control group.…”
Section: Discussioncontrasting
confidence: 71%
“…This HL deterioration rate is comparable to the hearing deterioration rate in a normal hearing control population. A previous report stated that patients with TECTA -associated mid-frequency HL might be prone to presbycusis as they are theoretically exposed to a lower level of sound energy as a result of cochlear amplification deficiency [36,37]. However, our results indicated that the hearing loss progression rate was the same as in the control group.…”
Section: Discussioncontrasting
confidence: 71%
“…In deafness pedigrees, variants affecting protein function in 12 genes were verified with the positive diagnostic rate 56.67% (17/30) ( Table 3). Detailed information on these deafness pedigrees is provided in our previous studies [22][23][24][25][26][27][28][29].…”
Section: Positive Diagnostic Rate For Snvsmentioning
confidence: 99%
“…6). At present, the TECTA gene mutations reported in the literature mostly occur in Iraq Lang family and Japanese family, with only four variation reported in Chinese family, including c.257_262delinsGCT [23], c.990C > A [24], c.5945C > A [25], and c.1893C > T [26]. Due to a lack of genetic screening, the mutation rate of TECTA in Chinese population still remains unknown.…”
Section: Discussionmentioning
confidence: 99%